POLITIK DINASTI DALAM KEPEMIMPINAN DESA (STUDI DESA WANTIWORO KECEMATAN KABAWO KABUPATEN MUNA) - Asriani Asriani; Wawan Wawan; La Ode Muh. Karman (Journal Publicuho, 2021)
This study aims to determine the factors that lead to the occurrence of dynastic politics in village leadership in Wantiworo Village. The research method used is descriptive qualitative research. Data collection techniques were carried out through in-depth interviews (interviews), observation and document studies. Analysis of the data and informants that have been obtained was carried out qualitatively.The results of research on dynastic politics in village leadership (Study of Wantiworo Village, Kabawo District, Muna Regency) where the most influencing the occurrence of dynastic politics in Wantiworo Village are only two factors, including capital strength (economic), the economic ability of a village head is also a consideration in the nomination . Wealth owned by the village head is the basic capital to achieve a goal or victory. Then the power of the network (the family), the family of the village head does have quite a big influence in the community. For example, the former village head of La Ode Gafar is a religious figure and La Ode Kiji is a person who is quite respected in the community besides other important positions in the village that have kinship relations.